PREFERENSI NASABAH DALAM MEMILIH PRODUK PERBANKAN PADA BANK 9 JAMBI SYARIAH - Maulana Yusuf; Devi Dewita; Syahril Ahmad (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Customer preference is the attitude of customers who want a product or service based on their ability to provide satisfaction value with what is purchased or offered, For this reason, this study aims to find out how customers prefer financing products and also to find out the factors that affect customer preferences for choosing financing products at Bank 9 Jambi Syariah Jambi City. This study uses a descriptive qualitative approach based on primary data (through interviews), It is also supported by library research which aims to collect data or information with the help of various references. The results of the study show that customer preferences for choosing financing are activities based on religious beliefs. The informants felt comfortable using Indonesia's Islamic banks for this financing. In addition, some informants stated that they felt it was more profitable to use the profit-sharing system and did not have high interest rates like conventional banks so that customers felt that they were not focused on the financing provided by Bank 9 Jambi Jambi City then associated with factors that influenced customers to choose financing products, namely, social factors, personal factors, price factors, and psychological factors as the customer's choice.